Budaya Organisasi, Motivasi Kerja Serta Kepuasan Kerja Dalam Meningkatkan Kinerja Pegawai Sekretariat Daerah Sulawesi Selatan - Fitrawati; Umar Congge (CV ODIS, 2021)
The purpose of this research is to know the influence of organizational culture, work motivation, and job satisfaction on the performance of Clerk At the regional secretariat for South Sulawesi province which consists of organizational culture, work motivation, and job satisfaction. The population in this study was an employee at the regional secretariat for South Sulawesi province with the number of samples as many as 86 people. The method of data collection in this study is a questionnaire, interviews, and documentation. Methods of data analysis using the method of descriptive and quantitative methods with multiple linear regression analysis used to measure the influence of organizational culture, work motivation, and job satisfaction on performance Clerk at the Secretariat The area of South Sulawesi province which consists of organizational culture, work motivation and job satisfaction. Based on a test of the free variable F (organizational culture, work motivation, and job satisfaction) simultaneously have a positive and significant influence against variables bound (employee's performance). Through testing (R) correlation coefficient obtained that level of correlation or relationship between organizational culture and work Motivation, job satisfaction is Employee Performance against a high relationship that is 98.3%. And the motivation of working is the most dominant factor influencing the performance of Employees On the regional secretariat for South Sulawesi Province.